Effectiveness of a nonoperative tailored treatment and return to sport of a rugby union player after a cervical spine disc herniation: a case report - Tondelli, Eduardo (2023)
Fil: Tondelli, Eduardo. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas; Argentina